International Civil Law Aspects of International Marriage: A Comparative Perspective of Indonesian and Japanese Law - Sugiastuti, Natasya Yunita; Rudyanto, Bambang; Dancar, Aleksander (Jambura Law Review, 2025)
International marriage is a marriage between two parties with different nationalities. As every country has its own civil law that regulates marriage, international marriage involves aspects of international civil law. This study raises two key issues: first, the determination of applicable laws related the material and formal conditions of marriage; and second, the citizenship of spouses as well as children in an international marriage. The discussionadopts a comparative perspective, focusing on Indonesian and Japanese legal systems.   This study employs normative legal research, utilizing a statutory and comparative approach, analyzing primary, secondary, and tertiary legal materials through qualitative methods and inductive conclusions. Results of the study indicate conceptual similarities between Indonesian and Japanese law in the area under study. First, material conditions of international/mixed marriage are determined based on the principle of lex patriae, while formal conditions are based on the lex loci celebration. principle Second, international marriage does not cause the spouses to automatically lose their own or obtain the citizenship of their spouse but can only obtain the citizenship of their spouse through a naturalization application. Children born in international marriages obtain citizenship based on the principle of ius sanguinis, and if this leads to dual citizenship, within a certain period of time the child must choose one of the nationalities. The existing literature concerning international marriage indicates that there is a gap of research with comparative approach between Indonesian and Japanese law. Thus, in addition to enriching the study of law related to international marriage, the results of this study can be used as educational materials for the Indonesian diaspora in Japan and vice versa.